لإطار المفاهيمي للعقار الصناعي في الجزائر كوسيلة لدعم المؤسسات الناشئة - شريفي, عماد; كشيش, عبد السلام (جامعة الوادي.University eloued, 2022)
تندرج هذه المداخلة ضمن المشاركة في فعاليات الملتقى الوطني الثاني عشر حول المؤسسات الناشئة والحاضنات، بالأساس في المحور الثالث بعنوان المعوقات التي تعترض المؤسسات الناشئة وحاضنات الأعمال، خصوصا في الجانب الإداري الذي يشكل فيه الوعاء العقاري الصناعي العقبة الكئود أمام المتعامل الاقتصادي الذي يرغب في الحصول على عقار صناعي يجسد فيه مشاريعه وابتكاراته العلمية، من أجل تحويلها إلى حقيقة عملية تصبح فيها المؤسسات الناشئة بمثابة رافعة اقتصادية يعول عليها في دعم التنمية المحلية وبناء اقتصاد معرفي واعدThis intervention falls within the participation in the activities of the Twelfth National Forum on Emerging Enterprises and Incubators, mainly in the third axis titled Obstacles to Emerging Enterprises and Business Incubators, especially in the administrative aspect in which the industrial real estate pot constitutes the major obstacle for the economic operator who wants to obtain real estate. An industrial project that embodies its projects and scientific innovations, in order to turn them into a practical reality in which emerging enterprises become a reliable economic lever in supporting local development and building a promising knowledge economy.
مجلد 01 العدد 01
Keywords: مؤسسات الناشئة، الوعاء العقاري، العقار الصناعي; Emerging institutions, real estate container, industrial real estate